The Venice Arsenal between history, heritage, and re-use - Zan, Luca (Routledge, Taylor & Francis Group, 2022)
History of management and stratigraphy of organizing / Luca Zan -- From manufacturing to industry: the turn in the late 19th century / Pasquale Ventrice -- The recovery of the Arsenal: the process from 1980 until today / Claudio Menichelli -- The role of the Agenzia del Demanio (State Property Agency) in enhancing the Arsenal / Ettore Cammarata -- The Società Arsenale di Venezia (SAV): from state control to municipal control / Roberto D'Agostino -- Some comments from a management studies perspective / Luca Zan -- Towards a museum of the Arsenal: home of Venetian civilization, history and shipbuilding / Camillo Tonini -- The Arsenal Museum: issues of spaces availability and accessibility / Franco Mancuso -- The National Museum of Naval History: a reconstruction of the project / Claudio Menichelli -- Scenarios for the Arsenal Museum: back to management / Luca Zan -- The Arsenal as intangible heritage: between historical meanings and re-uses / Luca Zan -- The Venice Arsenal, singular but not unique: towards a survey of Historic Naval Shipyards in Europe / Valentina Gambelli -- The heritization of Historic Naval Shipyards in Europe / Paolo Ferri, Pegram Harrison, Luca Zan -- Conclusions: a policy agenda to not forget / Luca Zan.
" ... contributions partly constitute work presented at two Ateneo Veneto conferences in 2017 and 2018 ..." (Introduction, Seite [1])
Keywords: Arsenale Venedig; Arsenale di Venezia / History; Arsenale di Venezia / Management / History; Urban renewal / Italy / Venice; Shipyards / History / Italy / Venice; BUSINESS & ECONOMICS / Nonprofit Organizations & Charities; ARCHITECTURE / Historic Preservation; Konferenzschrift -- 2017 -- Ateneo Veneto, Venedig; Konferenzschrift -- 2018 -- Ateneo Veneto, Venedig; Aufsatzsammlung